Assessment of gut microbiome, metabonome and characterization of enterococcus species from swine and farmers / Tan Shiang Chiet - Tan , Shiang Chiet (2021)
Gastrointestinal tracts of swine and farmers harbour a vast community of microorganisms which have enormous physiochemical and metabolic potentials. To date, study on the change of gut microbiome and metabonome in swine and farmers in response to their proximity remains scarce. Enterococcus faecalis (E. faecalis) and Enterococcus faecium (E. faecium) are members of the gut microbiota. They are opportunistic pathogens which can cause severe infections. The objectives of this study were: (i) to assess the gut microbiome and metabonome of swine and farmers, (ii) to investigate the effects of occupational exposure on the gut microbiome and metabonome of farmers, (iii) to characterize the phenotypes and genotypes of the isolated E. faecalis and E. faecium and (iv) to compare the genomics of selected E. faecalis strains via whole genome sequencing. This study utilized 16S rRNA metagenomics and 1H NMR metabonomics approaches to investigate the gut microbiome and metabonome of swine and farmers. The faecal samples of 140 swine and 24 farmers were collected from seven swine farms located in Peninsular Malaysia. Characterization of E. faecalis and E. faecium were performed by Pulsed-Field Gel Electrophoresis, Repetitive Extragenic Palindromic-PCR, antibiotic susceptibility test, biofilm assay and resistance- and virulence genes detection. Six representative E. faecalis strains were selected for Next Generation Sequencing. This study showed that the gut microbiota of swine and farmers were constituted by two major phyla, the Bacteroidetes and Firmicutes. Provotella spp. is a member of Bacteroidetes, which was detected as the major genus found in the gut of swine and farmers. Analysis on the faecal microbiota and metabolic profiles showed no significant difference between swine and farmers while significant difference was observed between human control cohorts and swine (P < 0.05). However, the relative abundance of Bacteroidetes and Firmicutes showed the gut microbiota of farmers was closer to swine. Notably, higher level of trimethylamine N-oxide (TMAO) and butyrate were detected in human control cohorts and swine, respectively. Integration study was used to illustrate the association network between the faecal metagenomics and metabonomics profiles. In this study, the concentration of TMAO found in the faecal sample was positively correlated to the relative abundance of Prevotella copri in the faecal sample. From the 164 samples isolated from swine (oral, urine and faecal), farmer (nasal, urine and faecal) and environment (pen swab, water and feed), 211 E. faecalis and 42 E. faecium were isolated. All the strains were multidrug-resistant and harboured various resistance and virulence genes. Phylogenomic analyses with reference to global strains revealed the Malaysian strains were clustered with clinical and environmental strains. Two strains, each from a swine and a farmer from the same farm were clustered, implying the possibility of strain transmission between animals and humans. In conclusion, the faecal microbiomes and metabonomes of swine and farmers were more similar than between the swine and human control cohorts. The livestock industry could be a reservoir of multidrug-resistant Enterococci as high occurrence of multidrug-resistant strains. Comparative genomic analyses of E. faecalis revealed a possibility of strains transmission between swine and farmers.